Peer observation, self-assessment, and circuit learning: improving critical thinking and physical fitness in physical education - Wahyu Indra Bayu; Nurhasan Nurhasan; Suroto Suroto; Soleh Solahuddin (LPMPP Universitas Negeri Yogyakarta, 2022)
Learning, which focuses on higher-level thinking skills, can be applied in the physical education curriculum through games and sports, movement education, and outdoor education. This study aims to produce a learning model that effectively improves the physical fitness and critical thinking skills of students. Purposive sampling was used in selecting research sample members in which 308 (M: 153 and F: 155) fifth-grade students participated in this study. Two groups were selected as research subjects divided into small groups for the first stage test (N: 123; M: 56; F: 67; Average age: 10.82) and large groups for the second stage test (N: 185; M: 97; F: 88; Average age: 10.70). Five indicators of critical thinking skills were measured through a critical thinking skills instrument. Meanwhile, the indicators of physical fitness tests include BMI, Sit and Reach, Sit-Up, Trunk Lift, and PACER 20-M. The results showed that physical education, oriented towards peer observation carried out during the learning process, self-assessment carried out by students, and packed in the circuit learning method is proven to improve critical thinking skills and physical fitness.